Modeling industrial embedded systems with UML - Fernandes, João M. (2000)
The main purpose of this paper is to present how the Unified Modeling Language (UML) can be used for modeling industrial embedded systems. By using a car radios production line as a running example, the paper demonstrates the modeling process that can be followed during the analysis phase of complex control applications. In order to guarantee the continuity mapping of the models, the authors propose some guidelines to transform the use case diagrams into a single object diagram, which is one of the main diagrams for the next development phases.